Методологічні аспекти моніторингу кадрового потенціалу вищого навчального закладу - Тугай, А. М.; Гойко, А. Ф.; Єлішевич, М. А.; Криштоф, С. Д.; Воронюк, О. І. (Ways to Improve Construction Efficiency, 2013)
The basic functions of monitoring of human resources of the university, the evaluation criteria and indicators of development.